Code-Crossing in Indonesian EFL Classroom Interaction - Simpuruh, Indrayani; Mahmud, Murni; Salija, Kisman; Halim, Abdul (International Journal of Language Education, 2020)
The phenomena of language use in the class still become the object of study ever since the languages are essential aspects in classroom interaction. It cannot be denied that in the classroom interaction, the communicative styles of the lecturers and students will be influenced by many aspects. One of them is the social status differences which lead to the occurrence of code-crossing in the class. For that purpose, the study in this paper is directed to explore the occurrence of code-crossing in the class and the factors influencing it. This research applied a qualitative research design taking two English classes and their students at one university in Makassar as the subject. The data of this research were collected by employing classroom observation and audio recording. The data were analyzed descriptively by adopting Discourse Analysis approach which relies on data recording, data transcription, data selection, and data interpretation. The result of the research shows that the lecturers and the students employed code-crossing in EFL classroom interaction which can be seen from the use of low and high code. This study also found that the use of that high and low code in the form of code-crossing of the lecturers and the students is influenced by the power of social status, age differences, the social distance or familiarity, and intimacy between the lecturers and the students. Findings from this study are worthy of reading for English language teaching practitioners in their effort to create effective classroom interaction.Â